Luminosity Studies for the Cool Copper Collider - Ntounis Dimitris; Nanni Emilio Alessandro; Vernieri Caterina (EPJ Web of Conferences)
Achieving high instantaneous luminosity while managing the beaminduced background (BIB) is critical for the successful operation of any future electron-positron (e+e−) collider. In this work, we summarize the first extensive luminosity studies for a proposed linear collider, the Cool Copper Collider (C3), which are originally presented in [1]. We evaluate the impact of key beam parameters on the luminosity of C3, and tune these parameters with the objective of optimizing the luminosity, without a commensurate increase in the accompanying BIB. Additionally, using a common simulation framework, we perform a comparative analysis of the luminosity and BIB characteristics of C3 with those for other linear colliders. Finally, we present preliminary results towards an automatized luminosity optimization scheme.